2023
DOI: 10.5964/jnc.10201
|View full text |Cite
|
Sign up to set email alerts
|

A direct comparison of two measures of ordinal knowledge among 8-year-olds

Chang Xu,
Jo-Anne LeFevre,
Sabrina Di Lonardo Burr
et al.

Abstract: Children’s knowledge of the ordinal relations among number symbols is related to their mathematical learning. Ordinal knowledge has been measured using judgment (i.e., decide whether a sequence of three digits is in order) and ordering tasks (i.e., order three digits from smallest to largest). However, the question remains whether performance on these two ordinal tasks tap into similar cognitive processes. Canadian children (N = 87; Age M = 8.7 years, Grade 3) completed symbolic number tasks (i.e., number comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, an alternative task does not exist yet, and because numerous studies have used the three-item order verification task, we believe it is still interesting to determine any ERP correlates associated with this task. An active ordering task, where participants need to sort a number of items, is popular in behavioral studies, especially with children (e.g., [ 47 ]), and might be employed in future EEG studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, an alternative task does not exist yet, and because numerous studies have used the three-item order verification task, we believe it is still interesting to determine any ERP correlates associated with this task. An active ordering task, where participants need to sort a number of items, is popular in behavioral studies, especially with children (e.g., [ 47 ]), and might be employed in future EEG studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, an alternative task does not exist yet, and because numerous studies have used the three-item order verification task, we believe it is still interesting to determine any ERP correlates associated with this task. An active ordering task, where participants need to sort a number of items, is popular in behavioral studies, especially with children (e.g., Xu et al, 2023), and might be employed in future EEG studies. Third, it is worth noting that we defined distance in unordered sequences relative to the first number, whereas distance in ordered sequences applies to both the first and second as well as the second and third numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, if the tendency to reject non-consecutive sequences does result from the task being too cognitively demanding, children who struggle on this task should still be able to indicate non-consecutive sequences as ordered in other contexts. Supporting this, Bugden and Brannon (2021) found that children who consistently rejected non-consecutive sequences during a standard order judgement task were still able to correctly produce ordered non-consecutive sequences during an order production task (for other examples of order production tasks, see Xu et al, 2023 ; Xu & LeFevre, 2021 ).…”
Section: Introductionmentioning
confidence: 93%